2022
DOI: 10.31234/osf.io/2r3ef
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimal resource allocation and its consequences on behavioral strategies, personality traits and preferences

Abstract: Life history theory is increasingly invoked in psychology as a framework for understanding differences in individual preferences. In particular, evolutionary human scientists tend to assume that, along with reproductive strategies, several behavioral traits such as cooperation and risk-taking and, in its broadest version, a range of psychological and personality traits also cluster into ‘fast’ and ‘slow’ life histories. However, the inclusion of such a wide range of traits in a life history strategy is founded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 134 publications
1
0
0
Order By: Relevance
“…We found that, as expected, higher morbidity and mortality risk perception was associated with less risk-taking. In line with recent work in behavioural ecology, our interpretation is that individuals want to minimize the chance of a loss in adverse contexts, and thus prefer the safer option [55]. People may want to minimize the economic risk they expose themselves to when they risk being sick, either directly because of the negative health shock, or indirectly because they expect to lose resources when they experience a negative health shock.…”
Section: Discussion and Limitationssupporting
confidence: 59%
“…We found that, as expected, higher morbidity and mortality risk perception was associated with less risk-taking. In line with recent work in behavioural ecology, our interpretation is that individuals want to minimize the chance of a loss in adverse contexts, and thus prefer the safer option [55]. People may want to minimize the economic risk they expose themselves to when they risk being sick, either directly because of the negative health shock, or indirectly because they expect to lose resources when they experience a negative health shock.…”
Section: Discussion and Limitationssupporting
confidence: 59%